2016
DOI: 10.1051/0004-6361/201628464
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the AGN in NGC 5548

Abstract: In 2013, we conducted a large multi-wavelength campaign on the archetypical Seyfert 1 galaxy NGC 5548. Unexpectedly, this usually unobscured source appeared strongly absorbed in the soft X-rays during the entire campaign, and signatures of new and strong outflows were present in the almost simultaneous UV HST/COS data. Here we carry out a comprehensive spectral analysis of all available XMM-Newton observations of NGC 5548 (precisely 14 observations from our campaign plus three from the archive, for a total of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 104 publications
(113 reference statements)
6
95
0
Order By: Relevance
“…This soft component was constant over the whole campaign, so it cannot be responsible for the variable soft excess we see here. Nonetheless, we added a similar component to our model (XSPEC model apec) with flux as in Cappi et al (2016) and found no improvement to the fit (c = n 1.16 2 for 1001 degrees of freedom). The best-fit spectra are shown in Figure 3 and the model parameters are given in Table 2 along with the flux in the soft X-ray excess after correcting for absorption.…”
Section: Spectra and Analysismentioning
confidence: 93%
See 3 more Smart Citations
“…This soft component was constant over the whole campaign, so it cannot be responsible for the variable soft excess we see here. Nonetheless, we added a similar component to our model (XSPEC model apec) with flux as in Cappi et al (2016) and found no improvement to the fit (c = n 1.16 2 for 1001 degrees of freedom). The best-fit spectra are shown in Figure 3 and the model parameters are given in Table 2 along with the flux in the soft X-ray excess after correcting for absorption.…”
Section: Spectra and Analysismentioning
confidence: 93%
“…The fit showed that the BB temperature is the same in the two spectra, so we tied the temperature and fitted the spectra again. The resulting fit was good (c = In their model of the entire XMM-Newton observing campaign, Cappi et al (2016) found an additional scattered soft X-ray component dominated by narrow emission lines, with 8% of the total soft X-ray flux. This soft component was constant over the whole campaign, so it cannot be responsible for the variable soft excess we see here.…”
Section: Spectra and Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…This scenario (hereafter called BLRscenario) nicely accounts for the X-ray emission variability of AGN 5 that occurs on very short time scales (from a fraction of a day up to years), and thus requires the absorber to be at sub-parsec distances from the X-ray source (e.g. Cappi et al 2016;Bianchi et al 2009;Risaliti et al 2005). It has been also proposed by Matt (2000) that while Compton-thick Seyfert 2 galaxies are observed through the torus, Compton-thin/intermediate Seyfert galaxies are obscured by dust lanes in the host galaxy.…”
Section: Modelling X-ray Emission In J1148mentioning
confidence: 99%